Iodine‐mediated expedient synthesis of sulfur–nitrogen‐containing heteroaminals under acidic condition. (6th March 2022) - More, Rameshwar M.; Kadam, Archana B.; Humne, Vivek T.; Junne, Subhash B.
Abstract: An unprecedented protocol for the synthesis of sulfur‐ and nitrogen‐containing heteroaminals from 2‐aminothiazole and pyrazole‐4‐carboxaldehyde using a combined catalytic amount of molecular iodine and acetic acid has been described. This represents the first report for the synthesis of acyclic heteroaminal which presumably proceed via the formation of Schiff base, get activated by using molecular iodine. All synthesized products are elucidated by spectral and mass analysis, obtained in good yield. Abstract : An unprecedented protocol for the synthesis of sulfur and nitrogen containing heteroaminals from 2‐aminothiazole and pyrazole‐4‐carboxaldehyde using a combined catalytic amount of molecular iodine and acetic acid has been described. This represents the first report for the synthesis of acyclic heteroaminal which presumably proceed via formation of schiff base, get activated by using molecular iodine. All synthesized products are elucidated by spectral and mass analysis, obtained in good yield.